The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3109/09638237.2013.841866
|View full text |Cite
|
Sign up to set email alerts
|

Meanings of well-being from the perspectives of youth recently diagnosed with psychosis

Abstract: Our heuristic framework for conceptualizing well-being, grounded in the narrative accounts of youth participants, can inform the future planning and design of interventions, research, and outcome measures pertaining to the well-being of youth recently diagnosed with psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 14 publications
1
17
0
1
Order By: Relevance
“…The self-help strategies reported by the participants are consistent with findings from studies that have shown that activities help change physical, emotional and cognitive states (Lal et al, 2013 ) and that meaningful activities and lifestyle modifications are factors influencing recovery (Windell & Norman, 2013 ) in early phases of mental health distress. The activities specifically mentioned as relieving and helpful in the present study (physical exercise, listening to music, experiencing nature, being with animals and work) have also all been reported as helpful in earlier recovery research (Borg & Kristiansen, 2008 ; Borg et al, 2013 ; Davidson et al, 2006 ; Lal et al, 2014 ; Lucock et al, 2007 ) and in the Nordic context (Borg & Davidson, 2008 ). In addition, the participants’ emphasis on a healthy and regular lifestyle and awareness of early triggers and warning signals are in line with earlier studies (Borg et al, 2009 ; Davidson et al, 2006 ; Suto et al, 2010 ; Veseth et al, 2012 ).…”
Section: Discussionmentioning
confidence: 51%
“…The self-help strategies reported by the participants are consistent with findings from studies that have shown that activities help change physical, emotional and cognitive states (Lal et al, 2013 ) and that meaningful activities and lifestyle modifications are factors influencing recovery (Windell & Norman, 2013 ) in early phases of mental health distress. The activities specifically mentioned as relieving and helpful in the present study (physical exercise, listening to music, experiencing nature, being with animals and work) have also all been reported as helpful in earlier recovery research (Borg & Kristiansen, 2008 ; Borg et al, 2013 ; Davidson et al, 2006 ; Lal et al, 2014 ; Lucock et al, 2007 ) and in the Nordic context (Borg & Davidson, 2008 ). In addition, the participants’ emphasis on a healthy and regular lifestyle and awareness of early triggers and warning signals are in line with earlier studies (Borg et al, 2009 ; Davidson et al, 2006 ; Suto et al, 2010 ; Veseth et al, 2012 ).…”
Section: Discussionmentioning
confidence: 51%
“…Resilience is generally understood as the capacity of an individual, family, community or environmental system to return to normative functioning after exposure to an atypical stressor (Ungar 2011;Allan and Ungar 2014). In the context of schools, resilience is observed when a student continues to engage and academically succeed even after he or she experiences a risk factor such as bullying or an episode of mental illness (Lal et al 2014). This understanding of resilience, which is centered on the individual or system that recovers from stress, has in recent years shifted to a more dynamic understanding of resilience as the quality of the interactions between systems and the resources they need to do well.…”
Section: A Social Ecological View Of Resiliencementioning
confidence: 99%
“…Qualitative investigations with young people diagnosed with FEP illustrate that they have a multi-dimensional perspective of their recovery and well-being that includes illness-related, social, moral, physical, and material or financial dimensions, and that meaningful activity engagement is also core to this process. [28][29][30][31] However, service providers may place more emphasis on symptom recovery and illness education, while not being attuned to addressing other aspects, such as social, physical, and meaningful activity engagement.…”
Section: Stakeholder Perspectives On Reasons For Disengagementmentioning
confidence: 99%